The exchange rate passthrough to domestic prices: New evidence from Colombia - Cristhian Larrahondo; Augusto Chávez; Laura Giles Álvarez; Leandro Andrián (Inter-American Development Bank (IDB), 2025)
This paper calculates the exchange rate pass through (ERPT) with time constant and time varying coefficients for Colombia between 2006 and 2023. It then estimates the ERPT during four specific depreciation events during the period of analysis: the 2008 financial crisis, the 2014-2016 fall in international fuel prices, the COVID-19 pandemic and the post-COVID recovery. A Bayesian Vector Autoregressive model with exogenous variables (BVARX) model with time constant and time varying coefficients is used for the exercise. The results for time constant coefficients show that a 1 percentage point (p.p.) increase in the depreciation of the exchange rate leads to an increase in imported, producer and consumer inflation of 0.42 p.p., 0.15p.p., and 0.01 p.p. respectively in the first month of the shock. Time varying coefficient results suggest that the nature and the size of the shock result in a heterogeneous ERPT and monetary policy response. Moreover, higher ERPT in imported inflation and producer inflation does not seem translate into higher ERPT in consumer inflation. Further studies could look at: First, the nature of the ERPT on different types of inflation and why this is heterogeneous in a time varying analysis. Second, how the combined effect of different factors in the Colombian economy led to different monetary policy responses in each of the four episodes under analysis.
Keywords: C32; C51; C52; E31; E44; E50; E52; F31; F41; 330; Passthrough; exchange rate; depreciation; prices; inflation; Colombia